An Improved Method for the Preparation of Copper Chlorophyll - Ramachandra Rao, P.; Naidu, P. S. B.; Pathak, T. C. (Indian Forester, 1956)
A method has been worked out for obtaining Copper Chlorophyll of a tinctorial value of 270-290.